CORRUPTION CRIMES FEATURES IN THE VOLGA FEDERAL DISTRICT - I. V. Il'yin; O. A. Korelov; S. N. Sukhov (Russian Journal of Economics and Law)
The article views the condition and basic trends of development of the operating situation in the Volga Federal District concerning the corruption crimes. The activity of law enforcement bodies in this aspect is studied. The general model of program measure for improving the law enforcement work is presented.